2008
DOI: 10.1523/jneurosci.1677-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

The Chemokine Stromal Cell-Derived Factor-1 Regulates GABAergic Inputs to Neural Progenitors in the Postnatal Dentate Gyrus

Abstract: Stromal cell-derived factor-1 (SDF-1) and its receptor CXC chemokine receptor 4 (CXCR4) are important regulators of the development of the dentate gyrus (DG). Both SDF-1 and CXCR4 are also highly expressed in the adult DG. We observed that CXCR4 receptors were expressed by dividing neural progenitor cells located in the subgranular zone (SGZ) as well as their derivatives including doublecortinexpressing neuroblasts and immature granule cells. SDF-1 was located in DG neurons and in endothelial cells associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
142
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(157 citation statements)
references
References 52 publications
(99 reference statements)
14
142
1
Order By: Relevance
“…Finally, the development of new generated neurons crucially depends on CXCL12, as it modulates axon growth and synapse formation by signaling through CXCR4. This signaling leads to the regulation of GABAergic inputs to NPCs from mature granule cells, thereby supporting the maturation of young neurons [46,47]. According to previous observations, our findings confirmed the expression of CXCR4 mRNA and the absence of CXCL12 mRNA in cultured NPCs.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, the development of new generated neurons crucially depends on CXCL12, as it modulates axon growth and synapse formation by signaling through CXCR4. This signaling leads to the regulation of GABAergic inputs to NPCs from mature granule cells, thereby supporting the maturation of young neurons [46,47]. According to previous observations, our findings confirmed the expression of CXCR4 mRNA and the absence of CXCL12 mRNA in cultured NPCs.…”
Section: Discussionsupporting
confidence: 88%
“…35 Further studies are required to determine the extent to which different CXCL12 isoforms contribute to the mechanisms of neuronal plasticity during reorganization of the ischemic hemisphere. Recently, it was demonstrated that CXCL12 affects the function of GABAergic neurons at the infarct boundary 39 and upregulation of CXCL12 in glial cells promotes differentiation of oligodendrocyte precursor cells, which are important for remyelination in the ischemic hemisphere. 40 While these potentially beneficial long-term processes require the activation of the CXCL12 pathway, our results show that immoderate excessive activation during the first week is detrimental for recovery of function after stroke supporting a dual role of this pathway after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Although the signaling mechanisms that regulate neurogenesis in the adult dentate gyrus have remained largely unknown, increasing evidence indicates that the proliferation and differentiation of NSCs in the dentate gyrus are influenced by neurotransmitters. Importantly, NSCs in the dentate gyrus receive GABAergic input (Bhattacharyya et al, 2008) that promotes their differentiation into neurons (Tozuka et al, 2005). Furthermore, GABAergic signaling decreases the proliferation of NSCs in the subventricular zone of the adult brain (Liu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%